Tularemia in Children: Evaluation of 22 Cases - Kars, Ayhan; Esmeray Şenol, Pelin; Köyceğiz, Sinan (Bilimsel Tip Publishing House, 2022)
Objective:Tularemia is a highly contagious bacterial zoonotic disease deriving from gram-negative Francisella tularensis. The disease is difficult for clinicians, and due to its rarity, a high level of suspicion is required for diagnosis. The purpose of the present study was to retrospectively examine the clinical characteristics, laboratory findings, and responses to treatment of pediatric tularemia cases treated in our clinic.
Keywords: 3. Good health